Effects of an ionic liquid and processing conditions on the β-polymorph crystal formation in poly(vinylidene fluoride). Issue 36 (14th August 2019) - Pickford, Tom; Gu, Xu; Heeley, Ellen L.; Wan, Chaoying
Abstract : The morphology, polar phase content and conductivity of PVDF nanofibres were enhanced by adding ionic substances to the electrospinning solution. Abstract : The piezoelectric properties of poly(vinylidene fluoride) (PVDF) are determined by the prevalence and orientation of its polar β-crystal phase, which can be tuned by processing conditions, additives, mechanical stretching or post-treatment. Here, the effects of three types of processing conditions on the crystalline structure evolution of PVDF were investigated; electrospinning, solution-casting and melt-compression. An ionic liquid (1-allyl-3-methylimidazolium chloride (AMIM)) used as an additive in aiding the electrospinning process, also affected the crystalline structure of the electrospun PVDF nanofibers. The total crystallinity, crystalline phase content and dielectric properties of the PVDF samples prepared by the different conditions were evaluated. The FTIR and DSC analyses show that the melt-compressed PVDF contains a high proportion of the paraelectric α-phase with a low total crystallinity, whereas the solution-cast PVDF contains a high proportion of polar γ-phase and a higher total crystallinity. In the case of the electrospun PVDF nanofibres, the addition of AMIM improved the morphology, uniformity and promoted the formation of the polar β and γ crystalline phases. X-Ray scattering analysis refined the crystal phase contents derived from FTIR, and also determined the ordered lamellar macromorphology formed by the three processing techniques. Furthermore, AMIM enhanced the a.c. conductivity and relative permittivity of the electrospun PVDF nanofibres by an order of magnitude, showing the effectiveness of using the ionic liquid AMIM, to improve the morphology and properties of electrospun PVDF nanofibers.